2021
DOI: 10.1021/acs.macromol.1c01214
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Origins of the Fracture Energy of Tough Double-Network Hydrogels with Quantitative Mechanochemical Characterization of the Damage Zone

Abstract: The high fracture energy of tough soft materials can be attributed to the large energy dissipation zone around the crack tip. Hence, quantitative characterization of energy dissipation is the key to soft matter fracture mechanics. In this study, we quantified the energy dissipation in the damage zone of a double-network (DN) hydrogel using a mechanochemical technique based on mechanoradical polymerization combined with confocal fluorescence microscopy. We found that, in addition to energy dissipation in a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…In the present work, the high toughness of our BSA/PAAm OHG may originate from the high viscosity of the mixture solvent (glycerol/H 2 O) and the plastic deformation of BSA biomacromolecules. Matsuda single-edge notch test and the controlled swelling PAAm hydrogel (ϕ PAAm = 28 wt %) estimated by a pure shear test were 343 J/m 2 and 500 J/m 2 , 40,41 respectively, which are lower than that of PAAm OHG in this work with a similar polymer content (T = 640 J/m 2 , ϕ PAAm = 30 wt %). The higher toughness of PAAm OHG may be caused by the glycerol.…”
Section: Mechanical Properties Of Bsa/paam Ohgsmentioning
confidence: 51%
“…In the present work, the high toughness of our BSA/PAAm OHG may originate from the high viscosity of the mixture solvent (glycerol/H 2 O) and the plastic deformation of BSA biomacromolecules. Matsuda single-edge notch test and the controlled swelling PAAm hydrogel (ϕ PAAm = 28 wt %) estimated by a pure shear test were 343 J/m 2 and 500 J/m 2 , 40,41 respectively, which are lower than that of PAAm OHG in this work with a similar polymer content (T = 640 J/m 2 , ϕ PAAm = 30 wt %). The higher toughness of PAAm OHG may be caused by the glycerol.…”
Section: Mechanical Properties Of Bsa/paam Ohgsmentioning
confidence: 51%
“…The high modulus ratio (hard to soft) increases the energy dissipation zone size, which is beneficial for improving the toughness. Besides, when such IR-WR samples are elongated, DND is preferentially destroyed, leading to a large energy dissipation, similar to the energy dissipation of a double network. Consequently, the toughness of IR-WR samples dramatically increases.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Mechanophore motifs that alter their optical properties with respect to applied loadmechanochromophores and/or mechanofluorophores (hereafter referred to as luminescent mechanophores)have emerged as the preferred tool to visualize such force-sensitive chain level behavior (Chen et al, 2021a;Göstl et al, 2017). Embedded luminescent mechanophores in elastomer networks have confirmed that chains located far from the crack surface (compared to the chain length) become ruptured during crack advance (Boots et al, 2022;Ducrot et al, 2014;Matsuda et al, 2020Matsuda et al, , 2021Slootman et al, 2020), supporting the postulated mechanism of dissipation and toughness enhancement. Unsurprisingly, viscoelastic effects and microscopic dynamics have been found to influence and interplay with the extent of delocalized chain scission measured via luminescent mechanophores (Slootman et al, 2020(Slootman et al, , 2022.…”
Section: Introductionmentioning
confidence: 90%